Correction: Wang et al. Calibration of DEM Polyhedron Model for Wheat Seed Based on Angle of Repose Test and Semi-Resolved CFD-DEM Coupling Simulation. Agriculture 2025, 15, 506 - Longbao Wang; Hanyu Yang; Zhinan Wang; Qingjie Wang; Caiyun Lu; Chao Wang; Jin He (Agriculture)
In the original publication [...]